Patani Scholars' Views on Tawassul with the Prophet and Righteous: Analysis of Abd al-Qadir bin Wangah's Risalah Irsyad Al-Jawiyīn - Katih, Isma-ie (International Journal of Nusantara Islam, 2023)
This study explores the theological concept of Tawassul in the Islamic tradition of the Nusantara region, focusing on Patani scholars' perspectives, particularly in Abd al-Qadir bin Haji Wangah Sela Budi Sekam Fatani's manuscript "Risalah Irsyad Al-Jawiyiin Ili Sabilil Al-Ulama' Al-‘Amilin." The manuscript's context is set in a period of theological debates between the Salaf and Khalaf schools, addressing Quranic interpretations, Hadith studies, and practices like Tawassul. The qualitative research methodology involves transcribing the original Jawi script into the Roman alphabet, translating it into English, and performing a detailed textual analysis. This approach aims to uncover the nuances of Tawassul, as discussed in the manuscript, making it accessible to a broader audience.The study reveals Tuan Guru Haji Abd al-Qadir's in-depth discourse on Tawassul, particularly relating to Prophet Muhammad Sallallahu’ alaihi wasallam and other righteous individuals. It underscores the permissibility and varied forms of Tawassul, reflecting the intricate layers of Islamic jurisprudence and cultural practices in the Nusantara region. The manuscript offers significant insights into the diversity of Islamic thought within the Nusantara region. It bridges historical theological discourse with contemporary religious practices, enriching the understanding of Tawassul's role in Islamic worship and spirituality. The study situates Tuan Guru Haji Abd al-Qadir's perspectives within broader Islamic theological discussions, highlighting the dynamic and interpretive nature of Islamic theology.